The Influence Of The Teacher's Ability To Use Computer-Based Media On Student Attention In Islamic Religious Education Learning At Public Junior High School (SMPN) 2 Sidrap - Muhammad Hijaz Tahir; Muhammad Arsal Hijaz; Sam Hermansyah (International Journal of Language and Ubiquitous Learning, 2023)
Background. Computer-based media enhances material acceptance and retention, facilitating teachers in efficient material storage and direct student engagement. Utilizing visuals and audio, it directly appeals to sight and hearing senses. Hence, the research titled "Effect of Computer-based Media Proficiency on Attention in Islamic Religious Education for Class VIII at Public Junior High School 2 Sidrap" is pertinent. Purpose. Based on some of these definitions both linguistically and in terms, teachers can be understood as people who are responsible for the development of students. Where the task of a teacher is to educate, namely to strive for the development of all the potential of students, both cognitive potential, affective potential and psychomotor potential. Method. This field research employs direct data collection and observation from respondents, falling under the quantitative category for obtaining objective, valid, and reliable numerical or scaled data. Utilizing associative research methods, its focus lies in establishing relationships between two or more variables. Results. The distributed questionnaires among students at Public Junior High School 2 Sidrap Regency revealed diverse attitudes toward the teacher's proficiency in utilizing computer-based learning media for Islamic Religious Education. Descriptive statistical analysis was employed to present and summarize the data through frequency distribution tables, aiming to provide a comprehensive overview aligned with the research objectives and variable descriptions. Conclusion. The study concludes that, based on questionnaire responses from 97 participants at Public Junior High School 2 Sidrap Regency, the teacher's proficiency in utilizing computer-based media for Islamic Religious Education learning (variable X) is at 79.9%, categorizing it as moderate. This determination is derived from a ratio of 7444 to 9312, signifying the identified criterion.